Cognitive impairment and associated factors among patients with diabetes mellitus in Africa: a systematic review and meta-analysis - Chekol Tassew, Worku; Ferede, Yeshiwas Ayal; Zeleke, Agerie Mengistie (Frontiers in Endocrinology, 2024)
Background: Inappropriate management of blood sugar in diabetes mellitus patients leads to micro-vascular and macro-vascular complications subsequently for high morbidity and mortality rates. In addition, diabetes independently increase the occurrence of cognitive impairment complicated with dementia. Scientific evidence on the magnitude of cognitive impairment will provide a sound basis for determination of health care needs and planning of effective health care service. Despite this, there is no comprehensive data on the prevalence and associated factors of cognitive impairment among patients with diabetes in Africa. Methods: To identify relevant articles for this review, we searched PubMed, Cochrane Library, Science Direct, African Journals Online, and Google Scholar. After extraction, the data was imported to Stata software version 11 (Stata Corp., TX, USA) for further analysis. The random effect model, specifically the DerSimonian and Laird (D+L) pooled estimate method, was used due to the high heterogeneity between the included articles. Begg’s and Egger’s regression tests were used to determine the evidence of publication bias. Sub-group analysis and sensitivity analysis were also conducted to handle heterogeneity. Results: The pooled prevalence of cognitive impairment among diabetic patients in Africa is found to be 43.99% (95% CI: 30.15 – 57.83, P<0.001). According to our analysis primary level of educational (POR=6.08, 95% CI: 3.57 – 10.36, I²=40.7%), poorly controlled diabetes mellitus (POR=5.85, 95% CI: 1.64 – 20.92, I²=87.8%), age above 60 years old (POR=3.83, 95% 95% CI: 1.36– 10.79, I²=63.7%) and diabetes duration greater than 10 years [POR: 1.13; 95% CI: 1.07– 1.19, I²=0.0%)] were factors associated with cognitive impairment among diabetic patients. Conclusion: Based on our systematic review, individuals with diabetes mellitus exhibit a substantial prevalence rate (43.99%) of cognitive impairment. Cognitive impairment was found to be associated with factors such as primary level of education, poorly controlled diabetes mellitus, age above 60 years, and a diabetes duration greater than 10 years. Developing suitable risk assessment tools is crucial to address uncontrolled hyperglycemia effectively.